Hierarchical architecture of spider attachment setae reconstructed from scanning nanofocus X-ray diffraction data. Issue 150 (31st January 2019) - Schaber, Clemens F.; Flenner, Silja; Glisovic, Anja; Krasnov, Igor; Rosenthal, Martin; Stieglitz, Hergen; Krywka, Christina; Burghammer, Manfred; Müller, Martin; Gorb, Stanislav N.
Abstract : When sitting and walking, the feet of wandering spiders reversibly attach to many surfaces without the use of gluey secretions. Responsible for the spiders' dry adhesion are the hairy attachment pads that are built of specially shaped cuticular hairs (setae) equipped with approximately 1 µm wide and 20 nm thick plate-like contact elements (spatulae) facing the substrate. Using synchrotron-based scanning nanofocus X-ray diffraction methods, combining wide-angle X-ray diffraction/scattering and small-angle X-ray scattering, allowed substantial quantitative information to be gained about the structure and materials of these fibrous adhesive structures with 200 nm resolution. The fibre diffraction patterns showed the crystalline chitin chains oriented along the long axis of the attachment setae and increased intensity of the chitin signal dorsally within the seta shaft. The small-angle scattering signals clearly indicated an angular shift by approximately 80° of the microtrich structures that branch off the bulk hair shaft and end as the adhesive contact elements in the tip region of the seta. The results reveal the specific structural arrangement and distribution of the chitin fibres within the attachment hair's cuticle preventing material failure by tensile reinforcement and proper distribution of stresses that arise upon attachment and detachment.